2017
DOI: 10.1080/00140139.2017.1288272
|View full text |Cite
|
Sign up to set email alerts
|

Systems scenarios: a tool for facilitating the socio-technical design of work systems

Abstract: The authors wish to acknowledge his tremendous contribution to the early drafts of this paper, and also to the field of organizational psychology and the design of sociotechnical systems, to which he dedicated his career. AbstractThe socio-technical systems approach to design is well documented. Recognising the benefits of this approach, organizations are increasingly trying to work with systems, rather than their component parts. However, few tools attempt to analyse the complexity inherent in such systems, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 57 publications
0
42
0
Order By: Relevance
“…In the long run, these practices will contribute to sustainable practices, the benefits of which will carry over successive projects. Overall our findings emphasize the need to embed communication elements within the emerging suite of sociotechnical and user-centered methodological tools (Hughes, Clegg, Bolton & Machon, 2017), which can be used as a point of reference by practitioners to help implement complex mHealth solutions.…”
Section: Macro-level Strategies For Increased Acceptance Of Lhwsmentioning
confidence: 75%
“…In the long run, these practices will contribute to sustainable practices, the benefits of which will carry over successive projects. Overall our findings emphasize the need to embed communication elements within the emerging suite of sociotechnical and user-centered methodological tools (Hughes, Clegg, Bolton & Machon, 2017), which can be used as a point of reference by practitioners to help implement complex mHealth solutions.…”
Section: Macro-level Strategies For Increased Acceptance Of Lhwsmentioning
confidence: 75%
“…Finally, the traditional approaches highlighted in Section 2.1 above have been criticised because they do not consider visibly and methodologically the human interactions with systems [6,46] which are inextricable parts of aircraft operations and are closely related to the development and application of MEL. Due to the interconnectedness of elements and processes that increase the complexity of modern systems, there is a need for more holistic and nonlinear frameworks to system safety analysis.…”
Section: Discussionmentioning
confidence: 99%
“…al. [46] recommends the Systems Scenarios Tool (SST), while Mumford [48] introduced the Effective Technical and Human Implementation of Computer based System (ETHICS) tool. Although each approach is accompanied by limitations in its endeavour to understand and deal with complexity, these tools suggest a more structured path to socio-technical systems modelling and offer a dynamic approach to systems safety engineering.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between colour and brand success has also been established in the literature . It may, therefore, be concluded that, in the areas of product and work system design as well as inclusive design (also known as universal design or design for all, which addresses the need for designing products and environments that meet the needs of the widest possible audience ‐ see, for example, http://www.inclusivedesigntoolkit.com), a more appropriate application of colour in the inclusive design of interfaces can have a significant impact on user performance and experience.…”
Section: Colour Ergonomicsmentioning
confidence: 97%